Evaluation of wind effects on a supertall building based on full scale measurements. - Li, Q.S.
This paper describes the results obtained from the full scale measurements of wind effects on a 70 storey building in Hong Kong. The building which has a height of approximately 370 m is the second tallest structure in Hong Kong. The field data such as wind speed, wind direction and wind induced acceleration responses have been measured since 1995 including the close passage of two typhoons; typhoon Sally and typhoon Kent. Detailed analysis of the field data is conducted. The full scale measurements are compared with the wind tunnel results obtained in the Boundary Layer Wind Tunnel Laboratory at Western Ontario University. The amplitude dependent characteristics of damping and natural frequency that were obtained by using the random decrement technique are investigated.
Keywords: Wind effect; Damping; Natural frequencies; Full-scale measurements; Wind tunnel test